Facts about Vitamin K - R. Elaine Turner; Wendy J. Dahl (EDIS)
Revised! FCS8666, a 3-page fact sheet by R. Elaine Turner and Wendy J. Dahl, answers common questions about this vitamin found mostly in green vegetables that is needed to make proteins for normal blood clotting. Includes references. Published by the UF Department of Family, Youth, and Community Sciences, October 2010.